Writing the Lives of Plants: Phytography and the Botanical Imagination. (2nd January 2020) - Ryan, John Charles
Abstract: Phytography refers to human writings about plant lives as well as plant writings about their own lives. The author conceptualizes phytography in terms of vegetal intelligence, behavior, corporeality, and temporality. Narrating the complex worlds of plants, phytography uses a variety of formal strategies to advocate new possibilities for human-flora relations.